1993
DOI: 10.1088/0953-4075/26/15/009
|View full text |Cite
|
Sign up to set email alerts
|

Positron impact ionization of atomic hydrogen

Abstract: Ionization cross sections for positrons impacting on atomic hydrogen have been measured for kinetic energies in the range 15-700 eV. This has been done in a crossed-beam geometry where a magnetically guided positron beam intersects a hydrogen gas jet emanating from a radio frequency discharge tube. Electron impact ionization cross sections were also measured with the same apparatus thus facilitating comparison with, and normalization to, published results. The positron-atomic hydrogen results are found to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 16 publications
8
48
0
Order By: Relevance
“…He þ Ps, which were treated in x 2.2.) The cross section for impact ionization of H was measured by Jones et al (1993) from threshold to 700 eV and confirmed by Hoffman et al (1997). These results are significantly lower than those of Spicher et al (1990), which were used by Wallyn et al (1994) in their study of annihilation in the ISM.…”
Section: Positron Energy Lossmentioning
confidence: 82%
“…He þ Ps, which were treated in x 2.2.) The cross section for impact ionization of H was measured by Jones et al (1993) from threshold to 700 eV and confirmed by Hoffman et al (1997). These results are significantly lower than those of Spicher et al (1990), which were used by Wallyn et al (1994) in their study of annihilation in the ISM.…”
Section: Positron Energy Lossmentioning
confidence: 82%
“…We base this belief on the fact that the CCC method is able to obtain quantitative agreement with the total ionization cross section for electron impact of atomic hydrogen [2], and that the model to which CCC has been employed is valid whenever the Ps formation cross section is negligible [6], which has been found to be the case above 100 eV by Sperber et al [7]. We therefore conclude that in this energy range the recent measurements of Jones et al [8] are likely to be the most accurate. Agreement with the total cross-section measurements down to 30 eV indicates that the model does not immediately break down once the Ps formation cross section is no longer negligible.…”
mentioning
confidence: 80%
“…In figure 2, the results are illustrated using the experimental results for H (Jones et al 1993), He and Ar (Moxom et al 1996), Ne, Kr and Xe (Kara et al 1997). The uncertainties concerning the absolute magnitude of the ionization cross sections of the inert gases by positron-and electron-impact (see Van Reeth et al 2002, Sorokin et al 1998 are irrelevant to the present discussion as the data are scaled to their peak value.…”
Section: Positron-impact Direct Ionizationmentioning
confidence: 99%